An Implementation Of Full-State Observer And Controller For Dynamic State-Space Model Of Zeta Converter - SARKAWI, HAFEZ; Jali, Mohd Hafiz (2013)
Zeta converter is a fourth order dc-dc converter that can increases (step-up) or decreases (step-down) the input voltage. The converter needs feedback control to regulate its output voltage. A full-state observer can be used to estimate the states of the system in condition the output must be observable. The estimated states can be fed to full-state feedback controller to control the plant. This paper presents the dynamic model of zeta converter. The converter is modeled using state-space averaging (SSA) technique. Full-state observer and controller are implemented on the converter to regulate the output voltage. The simulation results are presented to verify the accuracy of the modeling and the steady-state performance subjected to input and load disturbances.